2014
DOI: 10.3390/rs6098134
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes of Desertified and Managed Shrubland Landscapes in Response to Drought: Spectral, Spatial and Temporal Analyses

Abstract: Drought events cause changes in ecosystem function and structure by reducing the shrub abundance and expanding the biological soil crusts (biocrusts). This change increases the leakage of nutrient resources and water into the river streams in semi-arid areas. A common management solution for decreasing this loss of resources is to create a runoff-harvesting system (RHS). The objective of the current research is to apply geo-information techniques, including remote sensing and geographic information systems (GI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 88 publications
0
15
0
Order By: Relevance
“…Implementation of remote sensing for the identification of structural changes in shrublands in response to droughts was presented by Paz-Kagan [5]. A study of damages to Mediterranean forests in Israel has been reported by, among others, Volcani et al [48] and Dorman et al [49], the latter using a normalized-difference water index to represent water content in trees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementation of remote sensing for the identification of structural changes in shrublands in response to droughts was presented by Paz-Kagan [5]. A study of damages to Mediterranean forests in Israel has been reported by, among others, Volcani et al [48] and Dorman et al [49], the latter using a normalized-difference water index to represent water content in trees.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no information where such reduced rainfall had taken place, and what impact it had on natural ecosystems. According to existing studies, decreasing water availability is expected to reduce productivity in desert-fringe ecosystems in general and in semi-arid shrublands in particular [5][6][7][8]. This article aims at assessing trends of biomass change in the shrublands of the climatic gradient between sub-humid and arid zones in Central Israel as indicators of rainfall variations.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of longer satellite time series, covering the entire globe, such as the GIMMS dataset, has allowed the analysis of the relationships between climate variability on vegetation dynamics and crop yields both at global or continental scales (Lobell and Field, 2007, Gouveia et al, 2008, Zeng et al, 2013. Different studies for the Mediterranean analyzed the impact of droughts on the natural vegetation and crops using remote sensing data, Lloret et al (2007) and Vicente-Serrano (2007) in Northeast Spain, Lobo and Maisongrande (2006) in France, Gouveia (2009 and in Portugal, Dorman et al (2013), Trigo et al (2010) in the eastern Mediteranean area, Paz-Kagan et al, (2014) GlobCover classification over Mediterranean region was resampled for the GIMMS-NDVI spatial resolution (8 km) based on the mode rule for degradation of thematic maps (Figure 1). …”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In this study, one standard deviation (STD) was determined as a threshold based on previous experience with change detection analysis [53,56,57]. The direction of the change is computed by the angle (θ) of the change vector from the pixel value at these two dates:…”
Section: Cvamentioning
confidence: 99%